2018
DOI: 10.3835/plantgenome2017.07.0066
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genomic Loci Associated with Soybean Shoot Tissue Macro and Micronutrient Concentrations

Abstract: The mineral composition of crop shoot tissues is important for yield formation and nutrient remobilization to seeds. The natural diversity that exists within crop species can be used to investigate mechanisms that define plant mineral composition and to identify important genomic loci for these processes. The objective of this study was to determine shoot mineral nutrient concentrations in genetically diverse soybean [ (L.) Merr.] genotypes and to identify genomic regions associated with concentrations of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 156 publications
6
26
0
Order By: Relevance
“…Such relatively high broad-sense heritability suggested that the phenotype was largely determined by the genotypic effect [20]. Similar heritabilities for these traits have been reported in previous studies (H 2 = 0.48 to 0.93) [14,16]. In addition, a signi cant and positive correlation between the concentrations of K and P was observed (0.65, Table S1).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Such relatively high broad-sense heritability suggested that the phenotype was largely determined by the genotypic effect [20]. Similar heritabilities for these traits have been reported in previous studies (H 2 = 0.48 to 0.93) [14,16]. In addition, a signi cant and positive correlation between the concentrations of K and P was observed (0.65, Table S1).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, [16] also reported a QTL associated with the content in these two elements. Such correlations could be due to shared physiological mechanisms and metabolic pathways [4,21].…”
Section: Genome-wide Association Scan For Mineral Elements Content Inmentioning
confidence: 81%
See 3 more Smart Citations